Study of the Physicochemical Properties of Banana Tongka Langit Instant Powder Drink (Musa Troglodytarum L) With Arabic Gum Concentration Treatment Using Drying Foam Mat Method - LUMBAN TOBING, MARCHEL (Jurnal Sains dan Teknologi Pangan, 2023)
This study aims to characterize the physicochemical properties of the instant powder drink banana tongka langit with variations in the concentration of gum arabic as a bulking agent. This study was designed using a single-factor Complete Randomized Design (RAL) consisting of three levels of arabic gum consenstration treatment  , which is 15%, 20%, 25%. The results showed that the treatment of the addition of arabic gum concentration to the instant powder drink of banana tongka langit led to an increase in yield of 4.7%, water content of 1.63%, absorption capacity of 14.6%, soluble time of 37.67 seconds, insoluble part of 24.18%, vitamin C of 6.47%, and total solids of 1%.  The moisture content of the instant powder drink product banana tongka langit in this study has a value range of 3.67% – 5.30%. This water content value has met the requirements of SNI 01-4320-1996 regarding instant powder drinks, namely the water content is 3.0 – 5.0%. This shows that the banana tongka langit instant powder beverage product has met SNI and has good quality because it is very unlikely to be contaminated with microorganisms.